Phenotypic expression in hypertrophic cardiomyopathy and late gadolinium enhancement on cardiac magnetic resonance - Caetano, F (2014)
INTRODUCTION AND AIM: The prognostic value of late gadolinium enhancement (LGE) for risk stratification of hypertrophic cardiomyopathy (HCM) patients is the subject of disagreement. We set out to examine the association between clinical and morphological variables, risk factors for sudden cardiac death and LGE in HCM patients. METHODS: From a population of 78 patients with HCM, we studied 53 who underwent cardiac magnetic resonance. They were divided into two groups according to the presence or absence of LGE. Ventricular arrhythmias and morbidity and mortality during follow-up were analyzed. RESULTS: Patients with LGE were younger at the time of diagnosis (p=0.046) and more often had a family history of sudden death (p=0.008) and known coronary artery disease (p=0.086). On echocardiography they had greater maximum wall thickness (p=0.007) and left atrial area (p=0.037) and volume (p=0.035), and more often presented a restrictive pattern of diastolic dysfunction (p=0.011) with a higher E/É ratio (p=0.003) and left ventricular systolic dysfunction (p=0.038). Cardiac magnetic resonance supported the association between LGE and previous echocardiographic findings: greater left atrial area (p=0.029) and maximum wall thickness (p<0.001) and lower left ventricular ejection fraction (p=0.056). Patients with LGE more often had an implantable cardioverter-defibrillator (ICD) (p=0.015). At follow-up, no differences were found in the frequency of ventricular arrhythmias, appropriate ICD therapies or mortality. CONCLUSIONS: The presence of LGE emerges as a risk marker, associated with the classical predictors of sudden cardiac death in this population. However, larger studies are required to confirm its independent association with clinical events.